Multicenter retrospective analysis of systemic chemotherapy for unresectable combined hepatocellular and cholangiocarcinoma. Issue 8 (27th June 2018) - Kobayashi, Satoshi; Terashima, Takeshi; Shiba, Satoshi; Yoshida, Yukio; Yamada, Ikuhiro; Iwadou, Shouta; Horiguchi, Shigeru; Takahashi, Hideaki; Suzuki, Eiichiro; Moriguchi, Michihisa; Tsuji, Kunihiro; Otsuka, Taiga; et al.
Abstract : We conducted a multicenter retrospective analysis to evaluate the efficacy of systemic chemotherapy for unresectable combined hepatocellular and cholangiocarcinoma. We enrolled 36 patients with pathologically proven, unresectable combined hepatocellular and cholangiocarcinoma treated with systemic chemotherapy. The log‐rank test determined the significance of each prognostic factor. Elevated alpha‐fetoprotein, carcinoembryonic antigen and carbohydrate antigen 19‐9 levels were observed in 58.3%, 16.7% and 38.9% of patients, respectively. First‐line chemotherapy included platinum‐containing regimens consisting of gemcitabine/cisplatin (n = 12) and fluorouracil/cisplatin (n = 11), sorafenib (n = 5) and others (n = 8). The median overall and progression‐free survival times were 8.9 and 2.8 months, respectively, with an overall response rate of 5.6%. Prognostic factors associated with negative outcomes included poor performance status, no prior primary tumor resection, a Child‐Pugh class of B, and elevated carcinoembryonic antigen levels with a hazard ratio of 2.25, 2.48, 3.25 and 2.84 by univariate analysis, respectively. The median overall survival times of the gemcitabine/cisplatin, fluorouracil/cisplatin, sorafenib and other groups were 11.9, 10.2, 3.5 and 8.1 months, respectively. Multivariate analysis revealed that the overall survival of patients within the sorafenib monotherapy group was poor compared with platinum‐containing regimens (HR: 15.83 [95% CI: 2.25‐111.43], P = .006). All 7 patients in the sorafenib group had progressive disease, including 2 patients with second‐line therapy. In conclusion, the platinum‐containing regimens such as gemcitabine/cisplatin were associated with more favorable outcomes than sorafenib monotherapy for unresectable combined hepatocellular and cholangiocarcinoma. Abstract : We conducted multicenter retrospective analysis of systemic chemotherapy for unresectable combined hepatocellular and cholangiocarcinoma, because it is a rare type of cancer and only few case series were reported about systemic chemotherapy for the disease. Our results showed platinum‐containing regimen would be favor compared to sorafenib monotherapy and it supported the use of gemcitabine plus cisplatin which is a standard of care for unresectable cholangiocarcinoma.